2021
DOI: 10.2147/ijgm.s328882
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Neutrophil Percentage-to-Albumin Ratio and Outcomes in Cardiac Intensive Care Unit Patients

Abstract: Background The neutrophil percentage-to-albumin ratio (NPAR) is a systemic inflammation-based predictor associated with many diseases’ outcomes. Nevertheless, there are few studies on the relationship between NPAR and inflammatory markers, and more importantly, the prognostic value of NPAR in critically ill patients with cardiovascular disease (CVD) remains unknown. Methods The data of this retrospective cohort study were from the Medical Information Mart data for Inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…We conducted a single‐center retrospective cohort study; we collected all relevant data from Medical Information Mart for Intensive Care‐III (MIMIC‐III Version 1.4) 27–29 database. MIMIC‐III database is an open and freely available database developed by the Maslach‐setts Institute of Technology (MIT) computational Physiology Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a single‐center retrospective cohort study; we collected all relevant data from Medical Information Mart for Intensive Care‐III (MIMIC‐III Version 1.4) 27–29 database. MIMIC‐III database is an open and freely available database developed by the Maslach‐setts Institute of Technology (MIT) computational Physiology Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The data in the present study were obtained from the MIMIC-III database (version 1.4) 26,27 and included the definitive health records of more than 50,000 critically ill patients, who were admitted between 2001 and 2012, to the Beth Israel Deaconess Medical Center (Boston, MA, USA). The design of the database was approved by the Institutional Review Board of the Massachusetts Institute of Technology (Cambridge, MA, USA) and Beth Israel Deaconess Medical Center (Boston, MA, USA).…”
Section: Source Of Datamentioning
confidence: 99%
“…NLR and PLR were also identified to be associated with the prognosis of pulmonary embolism patients [ 10 ]. In a study by Wang et al, the increased NPAR level on admission was found to be associated with elevated all-cause mortality of patients in cardiac intensive care unit [ 11 ]. Additionally, PNI [ 12 ], PLR [ 13 ], NPAR [ 14 ], and NLR [ 15 ] were identified to be important prognostic biomarkers for AKI.…”
Section: Introductionmentioning
confidence: 99%